Evaluating Hots and Lots in '˜English for Nusantara': A Content Analysis of a Grade VII English Textbook - Fakhrillah, Agvy Rena; Suharyadi, Suharyadi (Universitas Pendidikan Mandalika, 2025)
In the 21st century, fostering critical thinking and problem-solving skills is essential for students. This study analyzes the manifestation of Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) in the English textbook '˜English for Nusantara' for Grade VII. HOTS involves higher-level cognitive processes such as analysis, evaluation, and creation, while LOTS focuses on recall and comprehension. Involving a qualitative research design with a content analysis approach, this study applied Revised Bloom's Taxonomy, which categorize exercises into LOTS (remember, understand, and apply) and HOTS (analyze, evaluate, and create). A total of 116 exercises in the form of instructions and 67 exercises in the form of questions from listening, speaking, reading, and writing tasks were analyzed. To maintain consistency, inter-rater reliability was ensured, where the analysis was cross-verified through discussions with a validator. The findings show that LOTS dominates the exercises, with 81% of the exercises are in the form of instructions and 89% in the form of questions. This indicates a heavy emphasis on LOTS and suggests an opportunity for more HOTS integration. Based on these findings, the study recommends that teachers incorporate more HOTS-focused activities, and textbook authors should design future editions with a stronger emphasis on HOTS exercises to foster critical thinking skills. Such adjustments would better equip students to meet the demands of the 21st century.